1997
DOI: 10.1302/0301-620x.79b5.0790727
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Healing of Simple Bone Cysts After Steroid Injections

Abstract: We reviewed 32 children after the treatment of simple bone cysts by intralesional injections of methylprednisolone acetate. The age of the child and the activity and size of the cyst did not significantly affect the radiological outcome. The earliest time at which the radiological response could be reliably determined was three months. After a median period of review of five years, four (13%) cysts had healed, 20 (62%) cysts were partially visible but sclerotic, four (12.5%) were still visible but opaque and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 18 publications
2
44
2
1
Order By: Relevance
“…All reported methods of treatment from massive subperiosteal diaphysectomy to simple percutaneous injection of steroid result in recurrence in a significant percentage of patients. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] It is accepted that the more radical the exci-sion of the cysts, the lower is the rate of recurrence. This benign self-limiting bone lesion does not seem to justify radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…All reported methods of treatment from massive subperiosteal diaphysectomy to simple percutaneous injection of steroid result in recurrence in a significant percentage of patients. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] It is accepted that the more radical the exci-sion of the cysts, the lower is the rate of recurrence. This benign self-limiting bone lesion does not seem to justify radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2) groups were satisfactory after several procedures, but were less impressive after a single procedure, especially in the steroid group. Other studies 14,15,25 have found that the healing response to steroid injection was unpredictable and usually incomplete. Scaglietti et al 24 noted that a single injection was sufficient to heal a bone cyst in only 24% of cases and Campanacci et al 14 found recurrence, or no response, after the initial injection in 32% of their patients.…”
Section: Classification Descriptionmentioning
confidence: 99%
“…Several other studies also suggested that repeated steroid injections may be needed to achieve adequate consolidation. 14,15,24,25 Autologous bone marrow grafting of unicameral bone cysts was introduced by Lokiec et al 6 in order to circumvent the repetition of steroid injections. Although grafting does not completely prevent recurrence, it has been reported 26,27 that the healing rate after a single bone marrow graft is about 60%.…”
Section: Classification Descriptionmentioning
confidence: 99%
“…These lesions are usually asymptomatic and the patient frequently presents with pathological fracture [3] at the time of diagnosis. Various methods of treatment of unicameral bone cysts have been proposed, treatment with open curettage with bone-grafting [4], intralesional injection of steroids [5, 6], autologous bone marrow [7, 8], percutaneous injection of allogenic demineralized bone matrix, and percutaneous curettage and bone grafting [9] with widely variable success rate. A successful treatment should give a higher healing rate, a short time to unite, and no recurrence.…”
Section: Introductionmentioning
confidence: 99%